2006
DOI: 10.1097/01.brs.0000232788.72321.63
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Cervical Spinal Cord in Patients After Spinous Process-Splitting Laminoplasty Using a Kinematic Magnetic Resonance Imaging Technique

Abstract: Spinous process-splitting laminoplasty increases the degree of freedom of the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Vertebral column kinematics is the study of the type and range of motion the vertebral column undergoes during normal movements . Kinematic studies can be performed in vivo and in vitro . Our group has worked to define the kinematic motion patterns of the canine cervical vertebral columns, with a particular emphasis on identifying differences between the cranial (C2–C4) and caudal (C5–C7) segments .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebral column kinematics is the study of the type and range of motion the vertebral column undergoes during normal movements . Kinematic studies can be performed in vivo and in vitro . Our group has worked to define the kinematic motion patterns of the canine cervical vertebral columns, with a particular emphasis on identifying differences between the cranial (C2–C4) and caudal (C5–C7) segments .…”
mentioning
confidence: 99%
“…We found that the kinematics of the cranial and caudal cervical vertebral columns differed markedly with greater mobility in the caudal cervical vertebral column . Biomechanical examination of isolated vertebral segments has also been performed in dogs to quantify effects of surgical alterations to the vertebral column …”
mentioning
confidence: 99%
“…In a similar study, Miyata et al [ 18 ] report changing L-values in 40 patients who underwent laminoplasty for symptomatic CSM. 20 of these patients had preoperative dMRI images which were used for controls, for a total of 60 scans.…”
Section: Discussionmentioning
confidence: 86%
“…Our search returned 19 articles which met criteria for inclusion in this review [ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ], 7 of these were retrospective analyses; the remainder were prospective studies. 2661 total patients were included in this review, with an average age of 52.9 years (range, 15–93 years); 49.5% of patients were male ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Laminoplasty has also been used to manage the decreased space occupied by the spinal cord caused by spondylotic bars, intervertebral disc hernia, ossification of the posterior longitudinal ligament, and/or a constitutionally narrowing cervical spinal canal [2,5]. When dynamic factors further reduce the functional diameter of the spinal canal, this contributes to the development of cervical myelopathy [8,17]. Laminoplasty becomes a feasible posterior decompression procedure for the cervical spinal cord as an attempt to manage multisegmental cord compression.…”
Section: Discussionmentioning
confidence: 99%